EFFECTS OF BLACK SOLDIER FLY (hermetia illucens) LARVAE MEAL ON THE GROWTH PERFORMANCE OF BROILER CHICKENS - Mohammed, A.; Laryea, T. E.; Ganiyu, A.; Adongo, T. (UDS International Journal of Development, 2017)
An experiment was conducted using broiler finishers to determine the effects of black soldier fly larvae meal on their growth performance. Thirty-two (32) chicks (Cobb strain) were selected and randomly divided into 16 groups of 2 birds each. Kitchen waste was used as a bait to attract the flies. The larvae were self-harvested according to the design of the baiting apparatus. The larvae were toasted, sun-dried and milled into powder. The fly larvae meal replaced commercial fish meal at 0% and 33% in broiler finisher diets. Two treatments were tested using a Completely Randomized Design and each treatment replicated thrice. Birds were fed from 3 to 8 weeks of age. Feed and water were provided ad libitum. Data collected were subjected to a two-sample design using GenStat, and treatment effects compared by Studentized T-test. Birds fed the black soldier fly larvae meal had similar feed intake (P>0.05) to that of their counterparts fed the control diets. All birds obtained similar (P>0.05) live weight gains and feed efficiencies. Birds fed the larvae meal had higher (P<0.05) carcass dressing than their counterparts fed the control diet. There was a significant increase (P<0.05) in the levels of haemoglobin, packed cell volume and red blood cells of birds fed the larvae meal than their counterparts fed the control diet. Based on this study, it can be concluded that black soldier fly larvae meal had the potential to replace fish meal in broiler chicken diet and could replace fish meal up to 33.3% in their diet without adverse effect on growth performance. Keywords: Black soldier fly, Broiler chickens, Carcass yield, Growth, HaematologyÂ